Understanding the impact of different hand drying methods on viral aerosols formation and surface contamination in indoor environments - Moura, Ines B.; Bentley, Karen; Kaur, Kimrun; Wilcox, Mark H. (Frontiers in Public Health, 2025)
BackgroundAs COVID-19 restrictions were lifted, compliance with good hygiene practices has declined. Hand drying can help remove microbes that remain on hands following poor hand washing. We looked at the potential of new electric hand dryer models to disperse microbial droplets and aerosolized particles during hand drying, to understand if there is a potential infection risk.MethodsWe used both a food dye solution and a bacteriophage solution to visually and quantitively investigate the potential of electric hand dryers Airblade 9KJ (A9KJ), Airblade Wash & Dry (AW+D) and of paper towels (PT), to disperse water droplets in the washroom environment, potentially contaminating surfaces, the user, and a bystander. We also investigated whether microorganisms aerosolized during hand drying can contaminate facemasks of others sharing the same space, mimicking the risk of virus inhalation, up to 30 min post-hand drying.ResultsThe highest level of droplet contamination on the floor and walls was observed using the A9KJ hand dryer. Compared to PT, average wall contamination was 78 times higher with A9KJ, and 19 times higher with AW+D. Hand drying assays using bacteriophage showed significantly less splattering contamination of both masks and torso when using PT, compared with electric hand dryers’ use. Overall, person contamination was 100- to 1,000-fold lower at the hand dryer position when using PT. Mask contamination of participants standing at 1 m distance of the hand drying unit was 10-fold and 100-fold lower in assays using PT, compared to A9KJ hand dryer and AW+D wall hand dryer use, respectively.ConclusionThe potential for virus spread via droplets and aerosols was considerably higher following the use of electric hand dryers, suggesting users are more at risk of contact with viral particles via touching contaminated surfaces or inhalation when using electric hand dryers, compared with PT.